Biochemical diversity of 12 Pistacia lentiscus oil growing in Algeria and there antimicrobial effect. - amel, Chemani; Abd el kader, aissat; Sidi mohamed, Ounane (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
Pistacia lentiscus oil is used in traditional medicine. The purpose of the present study was to determine if the Pisatcia lentiscus oil is of any interest for human nutrition and pharmaceutical industry. For this purpose, the physico-chemical properties of the oils of P. lentiscusfrom 12 localities of Northern Algeria were studied and compared as well as their compositions in free fatty acids, total polyphenols, flavonoids and chlorophylls.The agar well diffusion method and broth microdilution assay method are used to evaluate the antimicrobialand the antifungal activity of the 12 oils against 8 referenced microorganisms. Minimum inhibitory concentration (MIC) and Minimum Bactericidal Concentration (MBC)were calculated. Results showed that Pistacia lentiscusoilhas similar physico-chemical properties as virgin olive oil with an acid index around :3,5 ; a peroxide index around : 6, a saponification index between 179 and 200mg/g oil. And these oils were rich in chlorophyll, flavonoids and total polyphenols. Micrococcus luteus and Staphylococcus aureus have a sensibility against Pistacia lentiscus oils. An antibacterial effect was noted against Micrococcus luteus with inhibition zone diameters reaching18,5 mm. The Minimum inhibitory concentration attains 2,5mg/mL for Aspergillus niger, in Bouira locality. Statistical analysis could not differenciate groups according to the origin. Pistacia lentiscus oil is rich in unsaturated fatty acids. This oil can be used for human nutrition, agro-industrial processing and for pharmaceutical industry.